Resistências e controles no PAIF/CRAS : o desafio de desnaturalizar práticas e inventar possíveis - Santos, Keli Lopes (2015)
This dissertation was done in the intersection of several trials in field of Social Assistance, both in work experiences, as in militancy spaces and popular participation. It is from these experiences that it is woven the axis of the research. The purpose is to discuss how the processes of resistance and the processes of life regulamentation are being performed in Protection Service and Integral Care to Family developed on the Reference Center of Social Assistance more specifically at Cariacica city, in the state of Espírito Santo, in the Social Assistance Policy field. The concepts of Michel Foucault of resistance and regulamentation of life are the main conceptual tools of this dissertation. Two main strategies of knowledge production were used. One of them was to analyze the researcher´s notes and memories. The other was the analysis of the material produced in the meetings with users and professionals in the period from July to November 2014. For this data production, it was used individual conversations and periodical meetings with groups of professionals who work or worked on Reference Center of Social Assistance at Cariacica city. Through these memories and conversations, it is possible to discuss the process of resistance and control from various points of analyses, such as: family, woman, work, sanitation, charity and right, risk and vulnerability, among others. With that, it is not intended to judge the practices, but to analyze its effects in the Social Assistance Field. During the research, it was noticeable that there are many social assistance policies in the Reference Center of Social Assistance and outside it as well, not only state policies, but also friendship and solidarity policies and rebel policies.